Learning Innovation: PBL-STEM 4H Ecobrick material Teaching for 7th Graders to Enhance Ecoliteracy - Hapipah, Hepi; Rubini*, Bibin; Permanasari, Anna; Kodama, Yayoi; Rachman, Indriyani (Jurnal Pendidikan Sains Indonesia, 2024)
Teaching materials that accommodate innovative learning to improve environmental literacy are currently essential. Development research has been conducted to develop and examine the effectiveness of ecobrick theme teaching materials in improving student ecoliteracy. The teaching materials are packaged with the PBL-STEM 4H model (project based learning- science, technology, engineering, and mathematics - head, heart, hand, and harmony). The research employs research and development method and ADDIE design (analysis, design, development, implementation, and evaluation). This research uses interview guidelines, observation questionnaire sheets, and environmental literacy instruments as research instruments. In the development stage, this research employs several science teachers in the Sukabumi Regency, as determined by purposive sampling. In the implementation stage, 7th-grade students of one secondary school in West Java were tested to evaluate the effectiveness of the teaching materials in improving eco-literacy. Teaching materials were developed using PBL-STEM learning steps characterized by 4H values. The teaching materials' validation results show high validity with a feasibility score of 87.2, including a very valid category. The CVI (content validity index) and CVR (content validity ratio) indexes of 0.995 and 0.990 are included in the valid category. Teacher response to teaching materials reaches 90.05, including the outstanding category. The implementation results show that using the developed teaching materials during learning can improve student eco-literacy.